1987
DOI: 10.1111/j.1600-0536.1987.tb02674.x
|View full text |Cite
|
Sign up to set email alerts
|

Contact dermatitis to rhodium

Abstract: Illpreservatives senes, and the eye drops revealed a strong positive reactiOn to Visum1dnatic fenilefnna® eye drops, wh1ch had been used at the time of the first ophthalmic exammatwn. These eye drops contam: trop1cam1de 0.5%, phenylephrme hydrochlonde 10%, sodium metab1sulfite 0.1 %, thwmersal 0.01% and water.The patch tests w1th these compounds revealed a strong positive reactiOn to phenylephnne hydrochlonde 5% pet. (supplied by Firma Diagent, Florence, Italy). Discuss1onWe report th1s case to pomt out the Im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…20.9: Selected data on the toxicity of PGM compounds (data from Moore et al 1975;IPCS 1991;Marquardt and Schäfer 1994 mostly combined reactions with other metals, primarily nickel, have been observed. There are also indications for a potential allergenicity of Rh (Bedello et al 1987; de la Cuadra and Grau Massanes 1991), but to date only a few case studies have been reported (Gebel 2000). Care must be taken when handling volatile compounds such as osmium OsO 4 and RuO 4 .…”
Section: 64mentioning
confidence: 99%
“…20.9: Selected data on the toxicity of PGM compounds (data from Moore et al 1975;IPCS 1991;Marquardt and Schäfer 1994 mostly combined reactions with other metals, primarily nickel, have been observed. There are also indications for a potential allergenicity of Rh (Bedello et al 1987; de la Cuadra and Grau Massanes 1991), but to date only a few case studies have been reported (Gebel 2000). Care must be taken when handling volatile compounds such as osmium OsO 4 and RuO 4 .…”
Section: 64mentioning
confidence: 99%
“…Occupational allergic contact dermatitis has been described in subjects working in the jewelry trade [Bedello et al, 1987;De la Cuadra and Grau-Massanés, 1991;De la Fuente et al, 2003], but there are no cases with immediatetype allergic asthma due to rhodium salts in the literature. The impact of rhodium salt sensitization in workers of precious metals refineries remains unknown, but it is likely that platinum salts are the primary allergen in these settings.…”
Section: Discussionmentioning
confidence: 99%
“…In this last application, it is mostly present in objects containing silver, white gold or platinum, owing to its silvery white colour. Rhodium is generally regarded as allergologically safe; however, there are a few reports of occupational contact dermatitis (1–3) and of contact sensitization related to the use of dental prostheses (4). , Our patient developed nickel allergy after having used a new pair of clip‐on earrings which were labelled as ‘hypoallergenic’ and ‘nickel‐free’.…”
Section: Discussionmentioning
confidence: 99%